Recombinant human IL-37 inhibited endometriosis development in a mouse model through increasing Th1/Th2 ratio by inducing the maturation of dendritic cells - Lijie Li; Zhouzhou Liao; Mingzhu Ye; Jianfa Jiang (BMC, 2021)
Abstract Background Endometriosis is a serious reproductive and general health consequences. Recombinant human IL-37 (rhIL-37) is an inhibitor of inflammation. Methods ELISA assay was performed to detect the concentration of cytokines. Flow cytometry was used to analyze cell proportion. Besides, qRT-PCR and western blotting assay were used to detect the level of gene and protein, respectively. Transwell co-culture system was used for the co-culture of dendritic cells (DCs) and CD4+T cells. Results Our data showed that rhIL-37 inhibited the development of ectopic lesions in the mice with endometriosis, increased Th1/Th2 ratio and induced DCs maturation. The co-culture system of DCs and CD4+T cells demonstrated that rhIL-37 increased Th1/Th2 cell ratio through promoting DCs maturation. Moreover, the expression of IL-4 in the DCs derived from healthy mice was inhibited by rhIL-37 treatment. rhIL-37 increased Th1/Th2 cell ratio through inhibiting IL-4 in DCs. Subsequently, our results proved that rhIL-37 promoted the maturation of DCs via inhibiting phosphorylation of STAT3. Activation of STAT3 could reverse rhIL-37-induced maturation of DCs. Conclusion Overall, rhIL-37 could protect against endometriosis through increasing the ratio of Th1/Th2 cells via inducing DCs maturation and inhibiting IL-4 expression in the DCs. Furthermore, rhIL-37 induced DCs maturation by inhibiting STAT3 phosphorylation. Our data confirmed the protective effect of rhIL-37 in endometriosis. These data may provide a novel idea for the treatment of the disease. Graphical abstract